Application of Behavioral Architecture Concept on Space Order Natural Laboratory - Hana Rosilawati; Risma Andarini (Universitas Muhammadiyah Sidoarjo, 2021)
Elementary school natural laboratory is one of the learning facilities for students to produce a quality learning process. The laboratory is also a place for teaching and learning through practicum methods that interact and observe with living things directly. This natural laboratory is designed with a spatial layout based on the concept of behavioral architecture. The location of this research in Nation Star Academy Elementary School, Surabaya. Natural laboratories are very important in supporting Science subjects so that teachers can be optimal in explaining natural science in real terms. The research method used are qualitative and analytical. The data used in these methods consist of literature studies, interviews, observations of similar objects, and documentation. The result of this research is the design of a natural laboratory as a support for Elementary School Science subjects with the concept of behavioral architectural design in space order laboratory, which directs user behavior in achieving more ergonomic and efficient space requirements.